CHITOSAN-BASED NON-PARTICULATE VACCINE DELIVERY, CHALLENGES, AND FUTURE DIRECTIONS - ARSHIYA SAIYYAD; POONAM I LAL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Vaccination, a cornerstone of modern medicine, faces challenges with traditional injection methods, including pain, safety concerns, and cold-chain distribution issues. This review explores the potential of chitosan-based non-particulate vaccine delivery systems as a patient-friendly and effective alternative. Chitosan, a biocompatible and biodegradable polysaccharide, offers inherent mucoadhesive properties and a positive charge, facilitating interaction with mucosal surfaces and negatively charged antigens. Non-particulate systems (solutions, films, and hydrogels) offer advantages such as simplified manufacturing, antigen stability, and controlled release. This review focuses on the properties of chitosan relevant to non-particulate vaccine delivery, including physicochemical characteristics (molecular weight, degree of deacetylation, viscosity) and biological properties (biocompatibility, biodegradability, antimicrobial/antiviral potential). It examines the formulation considerations for chitosan-based hydrogels, films, and solutions, highlighting their mechanisms of action and applications in mucosal vaccine administration. The review further addresses current challenges, such as dosage control and long-term stability, and discusses future opportunities for innovation in this rapidly evolving field, with an emphasis on recent trends in nasal and oral vaccine delivery.